Analysis of high-risk factors for hepatocellular carcinoma after sustained virological suppression of chronic hepatitis B - Jianna Zhang; Zhiqiang Lan; Kailu Zhu; Sijie Yu; Shibo Li; Yu Huang (BMC Cancer)
Abstract Chronic hepatitis B (CHB) patients who have sustained virological suppression (SVS) still develop hepatocellular carcinoma(HCC), and the risk factors for developing HCC in these patients are not fully understood. This study included a total of 5234 patients who achieved SVS. After SVS, the incidence rate of HCC was 1.9% in 1–8 years and 1.33% in 9–16 years. There was a significant difference between the two periods (P < 0.001). After 1–8 years and 9–16 years of SVS, after multivariate analysis and IPTW adjustment, the factors related to the occurrence of HCC were men, hypertensive patients, diabetes patients and high FIB-4 scores. In summary, patients with CHB who have achieved SVS may still develop HCC. Among them, men, hypertensive patients, diabetes patients and high FIB-4 scores should be listed as the key monitoring objects of HCC. Clinical trial number: Not applicable.